2022
DOI: 10.3390/ijms232113639
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Bacillus Velezensis Microbial Inoculants on the Growth and Rhizosphere Soil Environment of Prunus davidiana

Abstract: Microbial inoculants, as harmless, efficient, and environmentally friendly plant growth promoters and soil conditioners, are attracting increasing attention. In this study, the effects of Bacillus velezensis YH-18 and B. velezensis YH-20 on Prunus davidiana growth and rhizosphere soil bacterial community in continuously cropped soil were investigated by inoculation tests. The results showed that in a pot seedling experiment, inoculation with YH-18 and YH-20 resulted in a certain degree of increase in diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…According to the report, Pseudomonas and Bacillus co-bacterial agent promotes the growth of soybean and increases its yield [51]. The application of a mixture of Bacillus YH-18 and YH-20 can effectively improve the nutrient utilisation of continuous cropping soils, antagonise the pathogenic bacteria of plants, and bene t the plant growth [52]. Mixed bioinoculant MI of Bacillus, Pseudomonas, Streptomyces, and Trichoderma has the potential to enhance wheat growth and seed yield [53].…”
Section: Discussionmentioning
confidence: 99%
“…According to the report, Pseudomonas and Bacillus co-bacterial agent promotes the growth of soybean and increases its yield [51]. The application of a mixture of Bacillus YH-18 and YH-20 can effectively improve the nutrient utilisation of continuous cropping soils, antagonise the pathogenic bacteria of plants, and bene t the plant growth [52]. Mixed bioinoculant MI of Bacillus, Pseudomonas, Streptomyces, and Trichoderma has the potential to enhance wheat growth and seed yield [53].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the application of PGPR could promote plant growth by reforming the rhizosphere microbial environment [ 6 , 34 ]. In this study, we showed that LYGN1 treatment has the same trends.…”
Section: Discussionmentioning
confidence: 99%
“…The high addition of EM, such as M2 and M3, resulted in a significantly higher amount of soil microorganisms, bacteria, and fungi compared to the CK, particularly in 2019 ( Figure 2 ). The addition of EM might result in competition with those indigenous microorganisms and hinder the growth and development of specific pathogens ( Mallon et al, 2015 ; Shi et al, 2022 ). All of these activity would cause alterations in the composition of microorganisms in the soil.…”
Section: Discussionmentioning
confidence: 99%